DISPOSITION KINETICS AND DOSAGE REGIMEN OF INTRAVENOUSLY INJECTED KANAMYCIN IN BUFFALOES - T. Saeed, R. Ahmad, M. Nawaz1 and T. Iqbal (Pakistan Veterinary Journal, 2000)
Genetical variations in the local population apprise of the need for describing biodisposition and fate of drug in indigenous species and environments. Kanamycin is one of the extensively used antibiotics in veterinary clinics. Its disposition kinetics was investigated in local female buffaloes following intravenous dose of 5 mg/kg body weight. The blood samples collected at different time intervals were analyzed for kanamycin concentration by a microbiological assay. Two compartment model kinetics analysis of plasma kanamycin concentration versus time data revealed its rapid distribution and elimination with half life (t 1/2) 5.42 ± 0.39 hours (Mean ± SE). Total body clearance of Kanamycin in buffaloes was 2.59 ± 0.17 ml/min./kg body weights. To maintain the minimum inhibitory concentration (MIC) of 2 µg/ml of plasma, optimal dosage regimen of 11.8 mg/kg body weight for primary and 9.4 mg/kg body weight for maintenance to be repeated after 12 hours interval has been suggested in buffaloes.